ASSESSMENT OF THE EFFECTIVENESS OF BIOLOGICALLY ACTIVE ADDITIVESCOMPLEX IN THE ADAPTATION OF THE MILITARYAFTER PNEUMONIA - Чуркин, Дмитрий Владимирович; Гасендич, Екатерина Сергеевна; Долгошапко, Ольга Николаевна; Ластков, Дмитрий Олегович (Medicine in Kuzbass, 2016)
Objective – evaluating the effectiveness of dietary supplements on the basis of selenium and spirulina, vitamin and mineral complex, nutritional therapy in the adaptation of the military after community-acquired pneumonia.Methods. Three experimental groups were formed: Group 1 received vitamin and mineral complex, Group 2 – complex of spirulina supplements and dietary supplements of selenium and ascorbic acid, and Group 3 received dietary supplement spirulina. Control group received nutritional therapy. We determined the adaptation index by Garkavi L.H. and adaptive capacity by Baevskiy R.P. Studies were carried out on the day before the treatment and after 21 days. The study determined the average values, the average values deviations, the significance of differences between mean values was evaluated by Student's t-test.Results. The use of vitamin and mineral complexes allows to achieve significant reduction of adaptation index. The use of complex Spirulina plus selenium and ascorbic acid allows to achieve significant reduction in adaptive capacity to the level of satisfactory adaptation. Using only spirulina does not allow to achieve a satisfactory adaptation. Isolated nutritional therapy had no significant effect on the considered indicators.Conclusions: the military need to receive adaptogens after community-acquired pneumonia. A complex of biologically active supplements containing the combination with spirulina dietary supplement, selenium and ascorbic acid, can be recommended for this purpose.
Keywords: adaptation; the military; pneumonia; spirulina; selenium; vitamin and mineral complex